 Open in App
Not now

# Class 8 RD Sharma Solutions – Chapter 7 Factorization – Exercise 7.7

• Difficulty Level : Medium
• Last Updated : 27 Nov, 2020

### Question 1: Solve for factors of x2 + 12x – 45

Solution:

Given: x2 + 12x – 45

To factorize the following expression we have to find two numbers a and b such that a + b = 12 and ab = – 45

We know that :

15 + (– 3) = 12 and 15 * (-3) = – 45

Splitting the middle term i.e. 12x in the given quadratic equation we get:

x2 + 12x – 45 = x2 + 15x – 3x – 45

= x (x + 15) – 3 (x + 15)        [Taking the similar terms common]

= (x – 3) (x + 15)        [as (x + 15) is common]

### Question 2: Solve for factors of 40 + 3x – x2

Solution:

Given: 40 + 3x – x2

40 + 3x – x2 = -(x2 – 3x – 40)

To factorize the following expression we have to find two numbers a and b such that a+b = -3 and ab = – 40

We know that :

5 + (-8) = -3 and 5 * (-8) = – 40

Splitting the middle term i.e. -3x in the given quadratic equation we get:

-(x2 – 3x – 40) = -(x2 + 5x – 8x – 40)

= -(x (x + 5) – 8 (x + 5))       [Taking the similar terms common]

= -(x – 8) (x + 5)        [as (x + 5) is common]

= (-x + 8) (x + 5)

### Question 3: Solve for factors of a2 + 3a – 88

Solution:

Given: a2 + 3a – 88

To factorize the following expression we have to find two numbers a and b such that a+b = 3  and ab = -88

We know that :

11 + (-3) = 3 and 11 * (-8) = -88

Splitting the middle term i.e. 3a in the given quadratic equation we get:

a2 + 3a – 88 = a2 + 11a – 8a – 88

= a (a + 11) – 8 (a + 11)        [Taking the similar terms common]

= (a – 8) (a + 11)        [as (a + 11) is common]

### Question 4: Solve for factors of a2 – 14a – 51

Solution:

Given: a2 – 14a – 51

To factorize the following expression we have to find two numbers a and b such that a+b = -14  and ab = -51

We know that :

3 + (-17) = -14 and 3 * (-17) = -51

Splitting the middle term i.e. -14a in the given quadratic equation we get:

a2 – 14a – 51 = a2 + 3a – 17a – 51

= a (a + 3) – 17 (a + 3)          [Taking the similar terms common]

= (a – 17) (a + 3)          [as (a + 3) is common]

### Question 5: Solve for factors of x2 + 14x + 45

Solution:

Given: x2 + 14x + 45

To factorize the following expression we have to find two numbers a and b such that a+b = 14  and ab = 45

We know that :

5 + 9 = 14 and 5 * 9 = 45

Splitting the middle term i.e. 14x in the given quadratic equation we get:

x2 + 14x + 45 = x2 + 5x + 9x + 45

= x (x + 5) – 9 (x + 5)         [Taking the similar terms common]

= (x + 9) (x + 5)         [as (x+5) is common]

### Question 6: Solve for factors of x2 – 22x + 120

Solution:

Given: x2 – 22x + 120

To factorize the following expression we have to find two numbers a and b such that a+b = -22  and ab = 120

We know that :

-12 + (-10) = -22 and -12 * (-10) = 120

Splitting the middle term i.e. -22x in the given quadratic equation we get:

x2 – 22x + 120 = x2 – 12x – 10x + 120

= x (x – 12) – 10 (x – 12)          [Taking the similar terms common]

= (x – 10) (x – 12)          [as (x – 12) is common]

### Question 7: Solve for factors of x2 – 11x – 42

Solution:

Given:  x2 – 11x – 42

To factorize the following expression we have to find two numbers a and b such that a+b = -11   and ab = -42

We know that :

3 + (-14) = -11 and 3 * (-14) = -42

Splitting the middle term i.e. -11x in the given quadratic equation we get:

x2 – 11x – 42 = x2 + 3x – 14x – 42

= x (x + 3) – 14 (x + 3)          [Taking the similar terms common]

= (x – 14) (x + 3)          [as (x + 3) is common]

### Question 8: Solve for factors of a2 + 2a – 3

Solution:

Given: a2 + 2a – 3

To factorize the following expression we have to find two numbers a and b such that a+b = 2  and ab = -3

We know that :

3 + (-1) = 2 and 3 * (-1) = -3

Splitting the middle term i.e. 2a in the given quadratic equation we get:

a2 + 2a – 3 = a2 + 3a – a – 3

= a (a + 3) – 1 (a + 3)          [Taking the similar terms common]

= (a – 1) (a + 3)          [as (a + 3) is common]

### Question 9: Solve for factors of a2 + 14a + 48

Solution:

Given: a2 + 14a + 48

To factorize the following expression we have to find two numbers a and b such that a+b = 14  and ab = 48

We know that :

8 + 6 = 14 and 8 * 6 = 48

Splitting the middle term i.e. 14a in the given quadratic equation we get:

a2 + 14a + 48 = a2 + 8a + 6a + 48

= a (a + 8) + 6 (a + 8)          [Taking the similar terms common]

= (a + 6) (a + 8)          [as (a + 8) is common]

### Question 10: Solve for factors of x2 – 4x – 21

Solution:

Given: x2 – 4x – 21

To factorize the following expression we have to find two numbers a and b such that a+b = -4  and ab = -21

We know that :

3 + (-7) = -4 and 3 * (-7) = -21

Splitting the middle term i.e. -4x in the given quadratic equation we get:

x2 + 4x – 21 = x2 + 3x – 7x – 21

= x (x + 3) – 7 (x + 3)          [Taking the similar terms common]

= (x – 7) (x + 3)          [as (x + 3) is common]

### Question 11: Solve for factors of y2 + 5y – 36

Solution:

Given: y2 + 5y – 36

To factorize the following expression we have to find two numbers a and b such that a+b = 5 and ab = -36

We know that :

9 + (-4) = 5 and 9 *(-4) = -36

Splitting the middle term i.e. 5y in the given quadratic equation we get:

y2 + 5y – 36 = y2 + 9y – 4y – 36

= y (y + 9) – 4 (y + 9)          [Taking the similar terms common]

= (y – 4) (y + 9)          [as (y + 9) is common]

### Question 12: Solve for factors of (a2 – 5a)2 – 36

Solution:

Given: (a2 – 5a)2 – 36

(a2 – 5a)2 – 36 = (a2 – 5a)2 – 62

By using the formula (a2 – b2) = (a+b) (a-b)

(a2 – 5a)2 – 62 = (a2 – 5a + 6) (a2 – 5a – 6)

Now solving the second part i.e a2 – 5a + 6

To factorize the following expression we have to find two numbers a and b such that a+b = -5  and ab = 6

We know that :

-2 + (-3) = -5 and -2 * (-3) = 6

Splitting the middle term i.e. -5x in the given quadratic equation we get:

a2 -5a + 6 = a2 – 2a – 3a + 6

= a (a – 2) -3 (a – 2)          [Taking the similar terms common]

= (a – 3) (a – 2)          [as (a – 2) is common]

Now solving the first part i.e a2 – 5a – 6

To factorize the following expression we have to find two numbers a and b such that a+b = -5  and ab = -6

We know that :

1 + (-6) = -5 and 1 * (-6) = -6

Splitting the middle term i.e. -5x in the given quadratic equation we get:

a2 -5a – 6 = a2 + a – 6a – 6

= a (a + 1) -6(a + 1)          [Taking the similar terms common]

= (a – 6) (a + 1)          [as (a + 1) is common]

Since, (a2 – 5a)2 – 36 = (a2 – 5a + 6) (a2 – 5a – 6)

Substituting the values of (a2 – 5a + 6 ) and (a2 – 5a – 6 ) we get:

= (a – 2) (a – 3) (a + 1) (a – 6)

### Question 13: Solve for factors of (a + 7) (a – 10) + 16

Solution:

Given: (a + 7) (a – 10) + 16

(a + 7) (a – 10) + 16 = a2 – 10a + 7a – 70 + 16

(a + 7) (a – 10) + 16 = a2 – 3a – 54

To factorize the following expression we have to find two numbers a and b such that a+b = -3  and ab = -54

We know that :

6 + (-9) = -3 and 6 * (-9) = -54

Splitting the middle term i.e. -3x in the given quadratic equation we get:

a2 – 3a – 54 = a2 + 6a – 9a – 54

= a (a + 6) -9 (a + 6)          [Taking the similar terms common]

= (a – 9) (a + 6)          [as (a + 6) is common]

My Personal Notes arrow_drop_up
Related Articles